Alkene epoxidation catalyzed by vanadomolybdophosphoric acids supported on hydrated titania - Ingle, Rohit H.; Vinu, A.; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
Vanadomolybdophosphoric acids wet-impregnated oil hydrated titania (TiO(2) - xH(2)O), make ail efficient catalytic system for the epoxidation of a variety of alkenes with organic solvent extracted TBHP as the oxidant. By,in appropriate choice of solvent, the catalyst call be reused at least three times without much loss in the activity for subsequent runs. XRD shows that the heteropoly acid is uniformly dispersed over the support and up to 15 wt% loading of the heteropoly acid, no additional peak of the same call be seen in the XRD pattern of the catalyst. The reactivity varied with the nature of alkene but the major product was always the corresponding epoxide. The catalytic system is free of high temperature calcination steps and tedious multi-step procedures, normally encountered in the heter-ogenization of heteropoly acids. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: alkenes; epoxidation; heteropoly acids; TBHP; titania; vanadomolybdophosphoric acids